Evoked release of methionine enkephalin from tolerant/dependent enteric ganglia: paradoxical dependence on morphine. - Gintzler, A R (1987)
Experiments were performed in order to determine whether the state of tolerance to and dependence upon opiates is associated with changes in one or more of the characteristics of the electrically induced release of methionine enkephalin from enteric ganglia. Acute morphine pretreatment substantially reduces the magnitude of the evoked release of this peptide from opiate-naive ilea. However, the rate of the evoked release of enkephalin from morphine-pretreated, tolerant/dependent preparations is indistinguishable from that observed for untreated, naive ilea. Paradoxically, 15 min after acute in vitro withdrawal of morphine form such preparations, the presence of morphine appears to be prerequisite for the manifestation of electrically evoked release of methionine enkephalin. The evoked release of this peptide from ilea 60 min after withdrawal is no longer dependent upon morphine. Moreover, the magnitude of the increase in the rate of enkephalin release from these preparations is almost double that observed for opiate-naive ilea. These data indicate that the manifestation of opiate tolerance/dependence for the release of methionine enkephalin from enteric ganglia comprises several adaptive processes, the consequences of which can be observed at different stages of withdrawal.